The Association between Allergic Rhinitis and COVID-19: A Systematic Review and Meta-Analysis - Cong Xu; He Zhao; Yuwan Song; Jiamin Zhou; Ting Wu; Jingjing Qiu; Junxin Wang; Xicheng Song; Yan Sun (International Journal of Clinical Practice)
Objective. Previous studies have yielded conflicting results regarding the association of coronavirus disease 2019 (COVID-19) with allergic rhinitis (AR). Data on AR prevalence in COVID-19 patients are limited. Consequently, whether AR is a harmful or protective factor for COVID-19 patients remains controversial. Therefore, we analyzed the relationship between COVID-19 and AR. Methods. We systematically searched PubMed, Embase, Cochrane, and Web of Science databases for studies published between January 1, 2020 and January 11, 2022. We included studies reporting the epidemiological and clinical characteristics of COVID-19 and its incidence in patients with AR. We excluded letters, case reports, literature review articles, non-English language article, and non-full-text articles. The raw data from these studies were pooled into a meta-analysis. Results. We analyzed the results of nine studies. The prevalence of AR in patients with COVID-19 was 0.13 (95% confidence interval [CI] 0.04–0.25), with an overall I2 of 99.77%, P=0.24. COVID-19 patients with AR are less prone to severe disease (odds ratio [OR] = 0.79, 95% CI, 0.52–1.18, P=0.25) and hospitalization (OR = 0.23, 95%CI, 0.02–2.67, P≤0.0001) than patients without AR. Conclusion. Our data suggest that allergic rhinitis is a protective factor in patients with COVID-19.